Utilization of E-Learning in Islamic Religious Education Learning: Literature Review - Suhardiansyah Suhardiansyah; Dimas Wahyu Ramadhan; Ahmadi Ahmadi (Penerbit Presisi Pustaka, 2026)
This study aims to analyze the utilization of e-learning in Islamic Religious Education (PAI) through a literature review approach. The rapid development of information technology has significantly transformed educational practices, including the delivery of religious education, which has traditionally relied on conventional methods. E-learning emerges as an alternative learning medium that enhances flexibility, accessibility, and effectiveness in the teaching and learning process. This research employs a qualitative approach using a literature study method by examining various sources such as academic journals, books, and relevant articles. The data were analyzed through systematic steps, including data reduction, data display, and conclusion drawing. The findings indicate that the use of e-learning in PAI learning offers several advantages, including promoting students’ independent learning, expanding access to diverse learning resources, and supporting more interactive and innovative teaching methods. However, several challenges remain, such as limited technological competence among teachers and students, reduced face-to-face interaction that may affect affective and spiritual aspects, and infrastructure limitations. Therefore, the implementation of e-learning in Islamic Religious Education should be optimized through improving teachers’ digital competencies, developing learning media aligned with Islamic values, and providing adequate infrastructure to achieve effective learning outcomes.